Single-Point Adaptive Control Method for Urban Mixed Traffic Flow - Xuelian Liu; Huazhi Yuan; Jie Hu; Xinlong Jiao (Journal of Advanced Transportation)
In urban traffic, motor vehicles, nonmotor vehicles, pedestrians, and other traffic are mixed, which seriously affects the urban traffic efficiency. At the intersections of urban roads especially, the priority setting of various travel modes is crucial to improve the urban traffic efficiency. In the urban hybrid traffic system, the architecture and algorithm flowchart of the single-point adaptive control system for urban hybrid traffic flow are presented. The control effect of this method is verified by VISSIM software. The simulation results show that the traffic efficiency of the priority objects at the intersection is increased by 6.03%, and the overall traffic efficiency is also significantly improved. This method has a certain practical value.